El secreto de la arboleda - Lalana, Fernando, 1958-; Tello, Antonio (Madrid : Ediciones SM, 2002)
Ernesto received four failing grades this school year. While his friends go away on vacation, he has to spend the summer studying. His only consolation is being able to visit a grove. There he meets up with his classmate Marijuli. Ernesto brags that he is friends with a fairy. To their astonishment, they find one in a trunk of a tree. Thus begins the fantastic adventure.
"Premio Nacional de Literatura Infantil y Juvenil 1991."
Keywords: Fairies -- Fiction